Risk Factors Associated with Diabetic Neuropathy in Type 2 C Patients Referred to Diabetic Clinic of Golestan Hospital, Ahvaz, Iran - Seyed Ehsan Moahmmadianinejad; Hajie Bibi Shahbazian; Davood Kashipazha; Mehrdad Karimi; Morteza Oghbaei; Davood Shalilahmadi; Nooshin Mashhadizadeh; Mohammad Reza (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Diabetes mellitus is one of the most common endocrine diseases. It affects 5-8% of Iranian population and nearly 177 million people worldwide. The disease predisposes to multiple microvascular complications such as neuropathy; retinopathy and nephropathy. Of these; neuropathy is the most common complication.7% at the time of diagnosis and 50% in the patients with 25 years history of disease suffer from neuropathy. Neuropathy can lead to sensory disturbances; foot ulceration; cellulitis; steomyelitis; gangren and amputation. Some people with diabetes experience painful neuropathy leading to impairment of daily function. Autonomic dysfunction is another debilitating complication of the diabetic neuropathy. In this study the relationship between diabetic neuropathy and a number of risk factors was evaluated.Subjects and Methods: 150 patients with type 2 diabetes randomly referred to diabetic clinic of Golestan hospital; Ahvaz, based on Michigan Neuropathic Diabetic Scoring and the nerve conduction study were divided into two groups with and without neuropathy and their relationship with risk factors was evaluated.Result: From 150 patients with diabetes;39 patients experienced neuropathy and prevalence of neuropathy was 26%.in the study of neuropathy and various risk factors; significant correlation between neuropathy and Age(p<o.oo6); duration of disease(p<0.001); BMI(p<0.05)and MNDS(p<0.001) was ststistically remarkable.Conclusion: the study reports concluded statistically significant relationship between age;MNDS;duration of disease;retinopathy; hypertention and BMI;thus controlling of blood pressure and weight control;resulting in wheight loss and subsequent better control of glucose;can be causative in delation of diabetic neuropathy